Primary intracranial germ cell tumors in children: a report of eight cases and review of the literature - Akyüz, Canan; Köseoğlu, Vedat; Bertan, Vural; Söylemezoğlu, Figen; Kutluk, M. Tezer; Büyükpamukçu, Münevver (The Turkish Journal of Pediatrics, 1999)
This study was conducted to evaluate the signs and symptoms on admission, diagnosis, localization, therapy, and survival of patients with primary intracranial germ cell tumors (PICGCT). Eight patients with surgically confirmed PICGCTs were treated and followed up at Hacettepe University’s Department of Pediatric Oncology between 1974 and 1995.While one patient was admitted with a second recurrence of her disease, the others were admitted or referred primarily to our institution. In this period, 357 germ cell tumor and 684 primary intracranial malignant tumors were diagnosed and treated at our institution. Thus, PICGCTs comprised 1.1 percent of the primary intracranial malignant tumors and 2.2 percent of the germ cell tumors. There were four females and four males and the median age was eight years (13 months to 12 years). On admission, the most common symptoms were diabetes insipidus (3/8) and vomiting (3/8). One patient also and Down’s syndrome. Locations of the tumors were suprasellar in three, in the third ventricle in two, and in the cerebral parenchyma, and pineal and hypothalamic regions in the remainder. There were three germinomas, three malignant teratomas, and two mixed germ cell tumors. Only two patients could be treated with appropriate and adequate chemotherapy and radiotherapy. Three patients died: one in the postsurgical period, one after the third surgical approach and one 11 months after the diagnosis of progressive disease; three were lost to follow-up. The remaining two patients (with second recurrence and disseminated disease) are alive and without disease.Our experience with these patients demonstrated that appropriate and adequate chemotherapy is as effective a treatment as radiotherapy, even with recurrence of the disease.
Keywords: intracranial; germ cell; tumor; children